FORMATION OF HIGH SCHOOL STUDENTS’SAFE BEHAVIOUR WHILE TERRORIST ATTACKS - Veretenko, Tetiana; Trebe, Anton; Bieloliptseva, Olena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The attention is drawn to the possibility of terrorist attacks in Ukraine. The essence of safe behaviour during a terrorist attack is revealed in the article. The purpose of the article is to determine the rules of behaviour for high school students in the case of a terrorist attack, the action algorithm of high school students on receiving information about a terrorist threat; rules of safe behaviour in social networks, which are actively used by terrorists, who attack high school students to participate in their groups and terrorist acts; to present a formation program of high school students’safe behaviour while terrorist attacks and show its effectiveness.The results of the experimental implementation of the program for formation of high school students’safe behaviour during terrorist attacks and emergencies are analyzed after asurvey carried out. According to the results summarised a conclusion is made to activate social and pedagogical work in the field of forming students’safe behaviour while terrorist attacks and emergencies.